Formal error prediction: The evaluation of standard operating procedures in a large commercial transport aircraft - Li, Wen-Chin; Hsu, Yueh-Ling; Chang, Danny; Wang, Thomas; Harris, Don (Air Transport Research Society, 2009)
This research applies the latest formal technique for human error prediction - Human Error Template (HET) - to evaluate standard operating procedures for performing a go-around in a large commercial transport aircraft. HET was originally developed in response to the requirement for formal methods to assess compliance with the new large civil aircraft human factors certification rule introduced to reduce the incidence of design-induced error on the flight deck (EASA Certification Specification 25.1302). A total of 67 Aircraft B pilots participated in this study including 25 captains and 42 first officers. This research finds that there are three types of errors with high likelihood committed by pilots during performing go-around, ‘Fail to execute’; ‘Task execution incomplete’; and ‘Task executed too late’. Therefore, there is a raising need to investigate further impact to flight safety for such errors occurred. Many of the errors that were found were the types of errors that most pilots were aware of and have simply had to accept on the flight deck. It is hoped that human factors certification standards would help to ensure that many of these errors are not included on future aircraft.
Keywords: Design induced human errors; Hierarchical task analysis; Human error identification; Standard operation procedures